Analysis of Renewable Energy Potential in South Sulawesi, Indonesia - Felix Dwiputra; Fahmy Rinanda Saputri (Universitas Islam Raden Rahmat, Malang, 2024)
The COVID-19 pandemic led to a temporary reduction in global energy usage, offering a glimpse of environmental benefits. However, subsequent rebounding energy demands underscored the need for cleaner alternatives. This paper examines renewable energy options for Indonesia, focusing on South Sulawesi. The region boasts significant solar irradiation and hydropower potential, with biomass also offering viable energy generation. While wind power is less potent, certain areas with high wind speeds could benefit. Transitioning to renewable sources could mitigate environmental and health concerns, addressing pollution and temperature rise. By leveraging these abundant resources, South Sulawesi could secure sustainable energy while minimizing adverse impacts on both the environment and public health.